Functional Approaches to Language, Culture, and Cognition : Papers in Honor of Sydney M. Lamb - Lamb, Sydney M.; Lockwood, David G.; Fries, Peter Howard; Copeland, James E. (Amsterdam studies in the theory and history of linguistic science. Current issues in linguistic theory, 2000)
This volume contains functional approaches to the description of language and culture, and language and cultural change. The approaches taken by the authors range from cognitive approaches including Stratificational grammar to more socially oriented ones including Systemic Functional linguistics. The volume is organized into two sections. The first section 'Functional Approaches to the Structure of Language: Theory and Practice' starts with contributions developing a Stratificational model; these are followed by contributions focusing on some related functional model of language; and by articl.